Path Analysis on the Relationship Between Bio-psychosocial Factors During Gestational Period and Birthweight, Stimulation and Development in Children Aged 1-3 Years in Salatiga - Vistra Veftisia; Didik Tamtomo; Muhammad Akhyar (Journal of Epidemiology and Public Health, 2016)
Background: Bio-psychosocial condition during gestational period, such as maternal nutritional status, stress, education, and family income, may have significant impact on fetal growth and development. The purpose of this study was to determine relationship between bio-psychosocial factors during gestational period and birthweight, and the relationship between stimulation and development in children aged 1-3 years.Subjectsand Method: This was an analytic and observational study with case control design. A sample of 120 children aged 1-3 years was selected by fixed disease sampling with case: control ratio= 1:2. The exogenous variables were gestational maternal education and current maternal education. The endogenous variables were gestational family income, gestational maternal stress, current family income, maternal nutritional status,  birthweight, stimulation, and child development. The data were collected by a set of questionnaire and analyzed by path analysis on STATA 13.Results:Birthweight ≥ 2.500 gram(b= 0.96; 95%CI= –0.15-1.94; p=0.054) and stimulation (b= 0.43; 95% CI=– 0.30-0.89; p=0.067) had direct positive effect on child development. Gestational maternal education, family income, maternal stress, maternal nutritional status, had indirect effect on child development through birthweight.Maternal education and family income had indirect effect on child development through stimulation.Conclusion: Birthweight ≥ 2.500 gram and stimulation have direct positive effect on child development.Keywords: bio-psychosocial, gestational period, birthweight, stimulation, developmentCorrespondence: Vistra Veftisia. Faculty of Health Sciences, Ngudi Waluyo University, Ungaran, Central Java. Email: chan_viez@yahoo.comJournal of Epidemiology and Public Health (2016), 1(3): 154-163https://doi.org/10.26911/jepublichealth.2016.01.03.02